Determinación de la energía metabolizable y comportamiento productivo de la harina integral de soya boliviana de proceso hidrotérmico en carne de pollos - Luna Mercado, Ayda Cecilia (Sistémica, 2018)
This study was carried out to determine the nitrogen corrected Apparent Metabolic Energy (EMAn) for  poultry of hydrotherm processed full fat soybean meal ( FFSM), comparing the Total Collection and Crude Fiber techniques ( Experiment !) and secondly to evaluate the determined energy value through the broilerperformance ( Experiment JI). In Experiment !, 60 male Arbor Acres chicks were used in two treatments with three replicates of 1 O chickens each. EMAn determined by the collection method and crude fiber resulted in 3.463 ± 0.009 Mcal/kg and 3.411 ± 0.137 Mcal!Kg respectively with metabolizability rates of 65.06 and 64.07% espectively. There was no statistical difference between methods. In Experiment 11, 60 male and 60 female chickens were equally distributed in 4 treatments. Isoproteic and isocaloric diets were fed ata fixed leve! o/20% FFSMformulated at 90, 100, JJOand 1120% the energy value determined by the total collection method. Live weight gains increased (P< 0,05) with the dietsformulated at the 90 and 100% energy levels. Abdominal fat increased quadractically as utilization of metabolizable energy in the diets was improved. Experiment JI results confirm the EMAn values for FFSM determined in Experiment l.